Klimagegensätze in Südperu und ihre Auswirkungen auf die Vegetation - Richter, Michael (ERDKUNDE, 1981)
In southern Peru the climate is subject to several gross changes from the Pacific to the Highlands. The relatively cool coastal area, with small diurnal fluctuations of temperature and atmospheric humidity, is followed above the 800 m contour by the dry and warm Atacama Desert. From 2,000 m. above sea-level precipitation in creases while temperatures decrease over very short distances. In the Highland east of the volcanic cordilleras diurnal amplitudes are particularly high (30°C in August), but decrease again in the direction of Lake Titicaca (Fig. 3 a, b). A hygro-thermal climatic typology according to W. Lauer/P. Frankenberg (1978, slightly altered) with balancing of the hydrological cycle elucidates the rapid change of the climatic circumstances (Map 1). Results of microclimatic measurements at different altitudes above sea-level show (Figs. 6-8) that further marked accentuation of extreme values of the individual climatic factors occurs, especially at great altitudes. Particularly noteworthy are the diurnal fluctuations of the surface temperature above the 4,000 m.contour, which, thanks to the special radiation conditions, may rise to well over 60°C Since the plants are predominantly confronted with the surrounding microclimate (e.g. during the germination phase at the soil surface, in their adult state at the plant surface), the signs of adaptation vary greatly at the different stages of adaptation (Map 2). Xerophytes and lichen characterize the temperate climate of the coastal zone, succulents and dwarf shrubs the semi-desert above the largely barren Atacama. Hard and ericaceous foliage are typical phenomena in the tola heath of the western cordilleras. The xeromorphic characteristics of the puna grasses and the polster plants in the highland are evidence of the need for protection against extreme diurnal fluctuations of the surface temperatures and against high rates of evaporation. In the Titicaca region, however, the growth forms of the plants are less unusual; hemicryptophytes predominate here. This study attempts to elucidate the significantly more abrupt change in the climatic and plant-geographical change of forms at high altitudes on the fringe of the tropics than in mountains of middle and higher latitudes.